North-South Customs Unions and International Capital Mobility - Eduardo Fernández-Arias; Mark M. Spiegel (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper examines the implications of a North-South trade accord where investments in the Southern partner nation exhibit country risk. Our analysis demonstrates that North-South trade accords can serve as credibility-enhancing mechanisms that induce additional foreign capital inflows into Southern partner nations. The presence of sovereign risk changes the tradeoffs between trade creation and diversion, enhancing the potential for regional trade accords to increase the welfare of accord members.
Keywords: 330